Palestinian Patients with Cancer at King Hussein Cancer Center - Mansour, Razan; Amarin, Justin Z.; Al-Ani, Abdallah; Al-Hussaini, Maysa; Mansour, Asem (Frontiers in Oncology, 2022)
Background: The Palestinian Ministry of Health (MoH) routinely refers Palestinian patients with cancer to the King Hussein Cancer Center (KHCC), the largest cancer center in the Middle East. Aims: We aimed to describe the characteristics of Palestinian patients with cancer. Methods: We performed a retrospective chart review of all Palestinian patients with cancer who were treated at KHCC during 2018 and 2019, of which demographic and clinical characteristics were presented. Results: We initially started with 521 cases, out of which 41 (7.9%) cases were excluded due to misdiagnosis as malignant on pathology review. We included 480 patients with a confirmed diagnosed of cancer. Most patients were adults (88.8%) with a mean age of 50.0 ± 15.0 years ranging from 19 to 87 years. The most common cancer sites in adult men, who comprised 46.9% of the cohort were the hematolymphoid system (23.5%), followed by the digestive system (17.5%), and lung and pleura (11.5%). In women (53.1%), the most common cancer sites were the breast (46.0%), followed by the digestive system (15.0%), and the hematolymphoid system (10.2%). Children and adolescents accounted for 11.3% of the total cases, among which the hematolymphoid system was the most common cancer site (50%), followed by the brain (14.8%). About 36.0% of all patients presented with advanced-stage disease (i.e., distant metastasis). Conclusion: The most common cancer sites in our cohort are generally similar to data from the Palestinian territories. Many patients presented with advanced-stage disease, which signals the need for awareness campaigns and screening programs. Cancer is misdiagnosed in many patients as benign tumors. The limited resources and facilities including human resources remain important challenges to the proper and timely diagnosis and management of cancer among Palestinians living in the Palestinian Territories.